Aluminum alloy foil with heterogeneous structure and preparation method and application thereof

By introducing Y elements into the aluminum alloy and controlling the structure to form a heterostructured aluminum alloy foil, the shortcomings in the elongation and strength of the existing aluminum foil are solved, and high strength, high elongation and high cup protrusion values ​​are achieved, which are suitable for soft packaging of lithium-ion batteries.

CN119753441APending Publication Date: 2025-04-04HUAFENG ALUMINUM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411949259.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing aluminum foil has shortcomings in elongation and strength, and it is difficult to meet the requirements of high elongation and high strength of lithium-ion battery flexible packaging.

Method used

By introducing Y elements into the aluminum alloy and controlling the structural morphology of the aluminum foil, an aluminum alloy foil with a heterostructure is formed, specifically including the coordinated distribution of fine crystals, coarse crystals and supercoarse crystals. The proportion of fine crystal structure is 42% to 56%, the proportion of coarse crystal structure is 40% to 53%, and the proportion of supercoarse crystal structure does not exceed 5%.

Benefits of technology

It realizes the high strength, high elongation and high cup protrusion value of aluminum alloy foil, and is suitable for flexible packaging of lithium-ion batteries, significantly improving the quality of soft-pack batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214459830000141
    Figure BDA0005214459830000141
  • Figure BDA0005214459830000151
    Figure BDA0005214459830000151
Patent Text Reader

Abstract

The present invention provides an aluminum alloy foil with a heterogeneous structure, a preparation method and an application thereof, wherein the material of the aluminum alloy foil is an aluminum-iron alloy, and the aluminum-iron alloy contains a Y element; the aluminum alloy foil has a heterogeneous structure, and the heterogeneous structure is mainly composed of a fine-grained structure and a coarse-grained structure, and the proportion of the ultra-coarse-grained structure does not exceed 5%; wherein the grain size of the fine-grained structure is less than or equal to 5 microns, the grain size of the coarse-grained structure is between 8 and 20 microns, and the grain size of the ultra-coarse-grained structure exceeds 20 microns and is less than 60 microns. The aluminum alloy foil provided by the present invention can have both excellent elongation after fracture and tensile strength, and can be well used in battery soft packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile battery materials, and in particular to an aluminum alloy foil with a heterogeneous structure and a preparation method and application thereof. Background Art

[0002] With the development of new energy vehicles, power batteries, as its key technology, have also received widespread attention. Among them, lithium-ion batteries are one of the main technical development directions of power batteries at present, and the market's attention and demand for them are gradually increasing. Aluminum-plastic film is an important material for encapsulating soft-pack lithium batteries, and plays a vital role in the quality of soft-pack batteries.

[0003] During the forming process of the aluminum-plastic film, it needs to go through a stamping process. The aluminum foil needs a certain elongation to ensure that the aluminum foil can be stamped smoothly. At the same time, it also needs to withstand a certain tensile stress. In addition, during the charging and discharging process of the battery, there will be a certain degree of expansion and contraction. The aluminum foil also needs to withstand corresponding tensile stress. This requires the aluminum foil to have a higher elongation while also having a higher strength.

[0004] CN111118351A discloses an aluminum foil, which has 0.05%-0.15% rare earth elements added therein, and has good ductility and strength, but the strength still needs to be improved. During the processing of the aluminum-plastic film, or during the use and transportation of the product after packaging, the aluminum foil will be subjected to a certain degree of tension. A higher strength means that the aluminum foil will not break easily when subjected to stress, so that the aluminum-plastic film can maintain a stable overall structure.

[0005] Therefore, there is an urgent need to develop an aluminum foil having both high elongation and strength. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an aluminum alloy foil with a heterogeneous structure and a preparation method and application thereof, by introducing the Y element into the aluminum alloy and regulating the organizational morphology of the aluminum foil to obtain an aluminum foil with high strength, high elongation and high cupping value.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an aluminum alloy foil with a heterogeneous structure, wherein the material of the aluminum alloy foil is an aluminum-iron alloy, and the aluminum-iron alloy contains the element Y; the aluminum alloy foil has a heterogeneous structure, and the heterogeneous structure is mainly composed of a fine-grained structure and a coarse-grained structure, and the proportion of the ultra-coarse-grained structure does not exceed 5%; wherein the grain size of the fine-grained structure is less than or equal to 5 microns, the grain size of the coarse-grained structure is between 8 and 20 microns, and the grain size of the ultra-coarse-grained structure is greater than 20 microns and less than 60 microns.

[0009] In aluminum-iron alloys, grain growth is achieved through the migration of grain boundaries. It is known that during annealing, when recrystallized grains encounter AlFe phases during growth, the AlFe phases can hinder the growth of recrystallized grains. When grain boundaries migrate, they will be hindered when encountering AlFe phases, thereby refining the recrystallized grains. Fe elements can be detected at the edges of coarse grains by EDS. The greater the number density of AlFe phases, the smaller the size of recrystallized grains. Therefore, the present invention reduces the probability of abnormal grain growth by controlling the number density of AlFe phases, thereby controlling the number of ultra-coarse grains.

[0010] In the annealed samples, some abnormally fine recrystallized grains were found by scanning electron microscopy. These recrystallized grains only appeared in the system containing Y. Such fine grains were not formed in the aluminum-iron alloy without Y. Bright white spots appeared in the center of the fine grains. EDS detected that the bright white spots contained Y elements; while there were no bright white spots on the coarse grains. It is speculated that in the matrix, recrystallized grains were formed by the precipitation phase containing Y as heterogeneous nucleation points. The precipitation phase of Y was basically formed during annealing and then triggered recrystallization. The size of such recrystallized grains is often very small, and there is a significant difference in size compared with conventional recrystallized grains.

[0011] The present invention adds Y element to the aluminum-iron alloy of the aluminum alloy foil, and generates a precipitation phase containing Y during annealing. The fine precipitation phase particles trigger the formation of fine crystals, and obtain grains of different sizes, thereby forming a heterogeneous structure with coordinated distribution of coarse and fine crystals. The heterogeneous structure described in the present invention is mainly composed of fine-grained structure and coarse-grained structure, and the proportion of ultra-coarse-grained structure is limited to no more than 5%; wherein, the fine-grained structure is a grain size less than or equal to 5 microns, the grain size between 8 and 20 microns is the grain size of the coarse-grained structure, and the grain size of more than 20 microns and less than 60 microns is the ultra-coarse-grained structure. In this alloy system, there is no grain size exceeding 60 microns.

[0012] For ultra-coarse grained structure, there are fewer grain boundaries, and dislocations are less hindered during movement, so they are easy to move, resulting in lower strength. During the cupping process, deformation is mainly concentrated at the grain boundaries. There are fewer grain boundaries around large grains, which makes the local stress concentration more obvious. When cupping is performed, this stress concentration may cause cracks in the material during a lower deformation process, reducing the cupping value of the aluminum foil. Therefore, the proportion of ultra-coarse grained structure needs to be controlled within a range of no more than 5% in order to increase the cupping value of the aluminum foil.

[0013] Specifically, the proportion of the ultra-coarse grained structure does not exceed 5%, for example, it can be 5%, 4.8%, 4.5%, 4.3%, 3.0%, 3.5%, 3.0%, 2.8%, 2.5% or 2.0%, etc.; wherein the grain size of the fine grained structure is less than or equal to 5 microns, for example, it can be 1 micron, 1.5 microns, 1.9 microns, 2.4 microns, 2.8 microns, 3.3 microns, 3.7 microns, 4.2 microns, 4.6 microns or 5 microns, etc., but is not limited to the listed values, and other values ​​not listed in the range are also applicable. The grain size of the coarse grained structure is between 8 The range of the present invention is as follows: the grain size of the ultra-coarse-grained structure is greater than 20 microns and less than 60 microns, for example, it can be 8 microns, 10 microns, 11 microns, 12 microns, 14 microns, 15 microns, 16 microns, 18 microns, 19 microns or 20 microns, but is not limited to the listed values, and other values ​​not listed in the range are also applicable. The grain size of the ultra-coarse-grained structure exceeds 20 microns and is less than 60 microns, for example, it can be 21 microns, 25 microns, 29 microns, 34 microns, 38 microns, 43 microns, 47 microns, 52 microns, 56 microns or 59 microns, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0014] Preferably, the proportion of fine-grained tissue in the heterogeneous structure is 42% to 56%, for example, it can be 42%, 43%, 45%, 47%, 49%, 52%, 54% or 56%, etc., but is not limited to the listed values, and other values ​​not listed within the range are equally applicable; and / or, the proportion of coarse-grained tissue in the heterogeneous structure is 40% to 53%, for example, it can be 40%, 42%, 43%, 45%, 46%, 47%, 48%, 49%, 50%, 52% or 53%, etc., but is not limited to the listed values, and other values ​​not listed within the range are equally applicable.

[0015] The coordinated distribution of fine grains and coarse grains in the structure of aluminum foil can improve the strength and elongation of aluminum foil. Fine grains have small grain size and large grain boundary area. During the deformation process, dislocation movement will be hindered by more grain boundaries, thereby increasing the strength. When fine grains are deformed under force, stress concentration will occur, causing the material to crack prematurely, resulting in a decrease in elongation. Coarse grains have large grain size and small grain boundary area, and have less resistance to crack propagation. Once cracks initiate, they can be relatively easy to expand quickly. Due to the low strength of coarse grains, initial cracks are easily generated, resulting in premature failure of the material, thereby reducing the elongation. When coarse grains and fine grains are distributed at the same time, the coarse grains around the fine grains can relieve stress concentration. The stress concentration generated when fine grains are deformed can be released in the coarse grain area. The coarse grains adapt to this stress change through their own deformation to avoid premature cracks in the material; and the presence of a large number of fine grains also prevents the material from cracking prematurely. This coordinated deformation improves the strength and elongation of aluminum alloys. However, when there are fewer fine crystals and more coarse crystals, too few fine crystals will lead to a decrease in material strength, and initial cracks will easily initiate. Once cracks initiate, they can expand relatively quickly and easily, causing premature aging of the material, thereby reducing the elongation. When there are more fine crystals and fewer coarse crystals, the stress concentration generated by the deformation of the fine crystals is difficult to release, resulting in cracks.

[0016] Preferably, in terms of mass percentage, the content of the Y element is 0.01-0.03wt%, for example, it can be 0.01wt%, 0.013wt%, 0.015wt%, 0.017wt%, 0.019wt%, 0.022wt%, 0.024wt%, 0.026wt%, 0.028wt% or 0.03wt%, etc., but is not limited to the listed values, and other values ​​not listed in this range are equally applicable; the content of the Fe element is 0.95-1.65wt%, for example, it can be 0.95wt%, 1.03wt%, 1.11wt%, 1.19wt%, 1.27wt%, 1.34wt%, 1.42wt%, 1.5wt%, 1.58wt% or 1.65wt%, etc., but is not limited to the listed values, and other values ​​not listed in this range are equally applicable.

[0017] If the Y element is not introduced into the aluminum-iron alloy, and the Y-containing precipitation phase is not generated, fine grains cannot be formed. When the Y element is introduced into the aluminum-iron alloy at a content of less than 0.01%, the number density of the precipitation phase formed is insufficient, and the proportion of fine crystals formed is insufficient. When the content of the introduced Y element is higher than 0.03%, the number density of the precipitation phase is too high, resulting in a large proportion of fine crystals formed; when there is too much Y element, at the minimum annealing temperature and time required to form complete recrystallization, the number density of the Y precipitation phase will still exceed the control value.

[0018] Fe is introduced into the aluminum-iron alloy to refine the recrystallized grains. When the Fe content is lower than 0.95wt%, the number density of the AlFe phase formed is insufficient, resulting in an excessively large proportion of ultra-coarse grains; when the Fe content is higher than 1.65wt% in the aluminum-iron alloy, the size of the AlFe phase is too large, resulting in a serious reduction in the strength and elongation of the material. Due to the relatively fast cooling environment (exemplarily 16°C / s) under the melting and casting process, the size of the AlFe phase that is inevitably formed is relatively large, and the number density of the AlFe phase is small. It is necessary to adjust the number density of the AlFe phase by crushing it by hot rolling. Although the large-sized AlFe phase can be crushed by hot rolling, when the Fe content is too high, some abnormal phases will be formed during the hot rolling process, which cannot follow the aluminum alloy matrix well to undergo plastic deformation, and are prone to cracking or separation from the matrix, and are difficult to be crushed.

[0019] The aluminum alloy foil contains a Y-containing precipitate phase and an AlFe phase. It is speculated that the Y-containing precipitate phase can trigger heterogeneous nucleation points, thereby affecting the generation and growth of recrystallized grains, while the AlFe phase affects the growth of recrystallized grains. The ratio of fine grains to coarse grains can be controlled by the number density of the Y-containing precipitate phase and the AlFe phase, thereby forming a heterogeneous structure with a coordinated distribution of coarse grains and fine grains. The number density of the AlFe phase is controlled to be about 60,000-72,000 / mm 2 ; The number density of Y-containing precipitates is about 1100-1600 / mm 2 .

[0020] Preferably, the maximum size of the AlFe phase is ≤10 microns, for example, it can be 10 microns, 9.8 microns, 9.5 microns, 9 microns, 8.6 microns, 8.5 microns, 8.2 microns, 8.0 microns, 7.5 microns, 7.0 microns, 6.5 microns, 6 microns, 5.5 microns, 5 microns, 4.5 microns, 4 microns, 3 microns, 2 microns or 1 micron, etc.

[0021] Large-sized AlFe phases will constitute material defects, which will not only fail to improve the mechanical properties by adjusting the grain size, but will also cause the strength and elongation of the material to be seriously reduced.

[0022] In a second aspect, the present invention provides a method for preparing the aluminum alloy foil having a heterogeneous structure according to the first aspect, the preparation method comprising:

[0023] (1) subjecting an aluminum alloy ingot to homogenization treatment to obtain a homogenized sample;

[0024] (2) After the homogenization treatment in step (1), the sample is sequentially hot-rolled and cold-rolled to obtain a rolled alloy;

[0025] (3) The rolled alloy in step (2) is annealed to obtain a finished aluminum alloy foil.

[0026] Preferably, the hot rolling temperature is 460-500°C, for example, it can be 460°C, 465°C, 469°C, 474°C, 478°C, 483°C, 487°C, 492°C, 496°C or 500°C, but is not limited to the listed values, and other values ​​not listed within the range are equally applicable, and / or, the total hot rolling reduction is 80%-93%, for example, it can be 80%, 82%, 83%, 85%, 86%, 88%, 89%, 91%, 92% or 93%, but is not limited to the listed values, and other values ​​not listed within the range are equally applicable.

[0027] Due to the faster cooling environment (exemplarily 16°C / s) under the melting and casting process, the AlFe phase that is inevitably formed is large in size and has a small number density of AlFe phase. It is necessary to adjust the size and number density of AlFe phase by crushing it through hot rolling. The temperature and reduction of hot rolling will affect the size and number density of AlFe phase. If the hot rolling temperature is too low, the plastic deformation capacity of the aluminum alloy is limited, the aluminum-iron phase is difficult to effectively refine, and there are large-sized AlFe phases with reduced number density. If the hot rolling temperature is too high, the solid solubility of Fe increases, and some aluminum-iron phases that were originally in a supersaturated state will dissolve back into the matrix, resulting in a decrease in the number density of the aluminum-iron phase. If the reduction is small, the crushing effect of the aluminum-iron phase is not obvious. If the reduction is too large, the edge of the material will be subjected to excessive tensile stress and crack.

[0028] Preferably, the annealing temperature is 280-300°C, for example, it can be 280°C, 283°C, 285°C, 287°C, 289°C, 292°C, 294°C, 296°C, 298°C or 300°C, but is not limited to the listed values, and other values ​​not listed within the range are equally applicable, and / or, the annealing time is 1-6h, for example, it can be 1h, 1.6h, 2.2h, 2.7h, 3.3h, 3.8h, 4.4h, 4.9h, 5.5h or 6h, but is not limited to the listed values, and other values ​​not listed within the range are equally applicable.

[0029] During the final annealing process, the temperature is set to 280-300°C and the time is 1-6h. On the one hand, during annealing, the fibrous structure (rolling formed) in the matrix is ​​induced to generate recrystallized grains, and the size of such grains is constrained by the distribution density of AlFe phase particles; on the other hand, Y-containing precipitation phases can be obtained during annealing, and the precipitation phases will trigger heterogeneous nucleation crystallization. Grains of different sizes are obtained through the precipitation phase, thus forming a heterogeneous structure with coordinated distribution of coarse grains and fine grains.

[0030] Sufficient annealing should be carried out. If the annealing temperature is too low or the time is too short, the recrystallization will be insufficient, or although the system is completely recrystallized, too little Y-containing precipitate phase will precipitate, resulting in a small proportion of fine grains. The Y element is mainly formed during the annealing process, and the number density of the Y-containing precipitate phase depends on the final annealing temperature and time, so that the number density of the Y-containing precipitate phase finally formed is within the target control range.

[0031] Excessive annealing should be controlled. When the annealing temperature is too high, part of the Y-containing precipitate phase may dissolve back into the matrix, thereby reducing the amount of precipitate phase, which is not conducive to heterogeneous nucleation crystallization, but instead the proportion of fine crystals is relatively small.

[0032] In a third aspect, the present invention provides an aluminum alloy foil with a heterogeneous structure as described in the first aspect, and / or an aluminum alloy foil made from the aluminum alloy foil with a heterogeneous structure as described in the second aspect, and use the aluminum alloy foil in a battery soft package, preferably in a lithium ion battery soft package.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects:

[0034] (1) The aluminum alloy foil with a heterogeneous structure provided by the present invention introduces a small amount of rare earth element Y into the aluminum-iron alloy, and controls the ratio of coarse grains and fine grains in the heterogeneous structure by using the Y element and combining the process, so that the strength of the alloy is improved while ensuring the elongation remains unchanged, wherein the elongation after fracture A50 of the aluminum alloy foil is above 20%, preferably above 23%; the tensile strength R m 105MPa and above, preferably above 114MPa;

[0035] (2) The method for preparing the aluminum alloy foil with a heterogeneous structure provided by the present invention introduces a specific annealing process, which changes the size and distribution of the Y-containing precipitate phase in the alloy, and can adjust the ratio of coarse grains and fine grains in the heterogeneous structure, thereby obtaining an aluminum alloy foil with high strength and high elongation;

[0036] (3) The aluminum alloy foil with heterogeneous structure provided by the present invention has excellent elongation and strength, and its application in lithium ion battery soft packaging can significantly improve the quality of soft package batteries. DETAILED DESCRIPTION

[0037] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] A specific embodiment of the present invention provides a method for preparing an aluminum alloy foil with a heterogeneous structure, the preparation method comprising the following steps:

[0039] (1) melting aluminum alloy raw materials of various components and weight percentages (the content of Y element is 0.01-0.03wt%; the content of Fe element is 0.95-1.65wt%), controlling the melting temperature within the range of 720°C-750°C, and then refining, standing and casting into aluminum alloy ingots; homogenizing the aluminum alloy ingots at 500-600°C for 2-20h to obtain homogenized samples;

[0040] (2) hot rolling the sample after the homogenization treatment in step (1) at a temperature of 460-500° C., with a total reduction amount of 80%-93%, hot rolling to a thickness of 2-6 mm, and then cold rolling to a thickness of 0.06-0.1 mm to obtain a rolled alloy;

[0041] (3) The rolled alloy in step (2) is annealed at 280-300° C. for 1-6 hours to obtain a finished aluminum alloy foil.

[0042] Example 1

[0043] This embodiment provides a method for preparing an aluminum alloy foil with a heterogeneous structure, the preparation method comprising the following steps:

[0044] (1) melting aluminum alloy raw materials of various components and weight percentages (the content of Y element is 0.02wt%; the content of Fe element is 1.05wt%), controlling the melting temperature within the range of 740°C, and then refining, standing and casting into aluminum alloy ingots; homogenizing the aluminum alloy ingots at 550°C for 10 hours to obtain homogenized samples;

[0045] (2) After the homogenization treatment in step (1), the sample is hot rolled at a temperature of 480° C., with a total reduction amount of 85%, hot rolled to a thickness of 4 mm, and then cold rolled to 0.08 mm to obtain a rolled alloy;

[0046] (3) The rolled alloy in step (2) is annealed at 290° C. for 3 h to obtain a finished aluminum alloy foil.

[0047] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 3.2%, a fine grain structure with a proportion of 52.1%, a coarse grain structure with a proportion of 44.2%, and a phase size of the AlFe phase with a phase size of 8.6 micrometers.

[0048] Example 2

[0049] This embodiment provides a method for preparing an aluminum alloy foil with a heterogeneous structure, the preparation method comprising the following steps:

[0050] (1) melting aluminum alloy raw materials of various components and weight percentages (the content of Y element is 0.01wt%; the content of Fe element is 0.95wt%), controlling the melting temperature within the range of 720°C, and then refining, standing and casting into aluminum alloy ingots; homogenizing the aluminum alloy ingots at 500°C for 20h to obtain homogenized samples;

[0051] (2) After the homogenization treatment in step (1), the sample is hot rolled at a temperature of 460° C., with a total reduction amount of 80%, hot rolled to a thickness of 2 mm, and then cold rolled to 0.06 mm to obtain a rolled alloy;

[0052] (3) The rolled alloy in step (2) is annealed at 280° C. for 6 hours to obtain a finished aluminum alloy foil.

[0053] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 4.3%, a fine grain structure with a proportion of 42.3%, a coarse grain structure with a proportion of 53.1%, and a phase size of the AlFe phase with a phase size of 8.5 micrometers.

[0054] Example 3

[0055] This embodiment provides a method for preparing an aluminum alloy foil with a heterogeneous structure, the preparation method comprising the following steps:

[0056] (1) melting aluminum alloy raw materials (the content of Y element is 0.03wt%; the content of Fe element is 1.65wt%) of each component and weight percentage, controlling the melting temperature within the range of 750° C., and then refining, standing and casting into aluminum alloy ingots; homogenizing the aluminum alloy ingots at 600° C. for 2 h to obtain homogenized samples;

[0057] (2) After the homogenization treatment in step (1), the sample is hot rolled at a temperature of 500° C., with a total reduction amount of 93%, hot rolled to a thickness of 6 mm, and then cold rolled to 0.1 mm to obtain a rolled alloy;

[0058] (3) The rolled alloy in step (2) is annealed at 300° C. for 1 h to obtain a finished aluminum alloy foil.

[0059] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 3.6%, a fine grain structure with a proportion of 56.2%, a coarse grain structure with a proportion of 40.0%, and a phase size of the AlFe phase with a phase size of 9.6 micrometers.

[0060] Example 4

[0061] This embodiment provides a method for preparing an aluminum alloy foil with a heterogeneous structure. The only difference from Embodiment 1 is that the content of the Y element in the aluminum alloy raw material is 0.04 wt %. The rest is the same as Embodiment 1.

[0062] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 2.8%, a fine grain structure with a proportion of 61.6%, a coarse grain structure with a proportion of 35.1%, and a phase size of the AlFe phase with a phase size of 8.9 micrometers.

[0063] Example 5

[0064] This embodiment provides a method for preparing an aluminum alloy foil with a heterogeneous structure. The only difference from Embodiment 1 is that the content of the Y element in the aluminum alloy raw material is 0.005 wt %. The rest is the same as Embodiment 1.

[0065] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 2.9%, a fine grain structure with a proportion of 34.5%, a coarse grain structure with a proportion of 62.5%, and a phase size of the AlFe phase with a phase size of 8.5 micrometers.

[0066] Example 6

[0067] This embodiment provides a method for preparing an aluminum alloy foil with a heterogeneous structure. The only difference from the embodiment 1 is that the annealing temperature is 270° C., and the rest is the same as the embodiment 1.

[0068] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 3.5%, a fine grain structure with a proportion of 36.5%, a coarse grain structure with a proportion of 59.3%, and a phase size of the AlFe phase with a phase size of 8.9 micrometers.

[0069] Comparative Example 1

[0070] This comparative example provides a method for preparing an aluminum alloy foil with a heterogeneous structure, which is different from Example 1 only in that the aluminum alloy raw material does not contain the Y element, and the rest is the same as Example 1.

[0071] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 3.6%, a fine grain structure with a proportion of 0%, a coarse grain structure with a proportion of 96.1%, and a phase size of the AlFe phase with a phase size of 8.5 micrometers.

[0072] Comparative Example 2

[0073] This comparative example provides a method for preparing an aluminum alloy foil with a heterogeneous structure, which is different from Example 1 only in that the Fe content in the aluminum alloy raw material is 1.7wt%, and the rest is the same as Example 1.

[0074] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 3.5%, a fine grain structure with a proportion of 56.1%, a coarse grain structure with a proportion of 40.1%, and a phase size of the AlFe phase with a phase size of 12.1 micrometers.

[0075] Comparative Example 3

[0076] This comparative example provides a method for preparing an aluminum alloy foil with a heterogeneous structure, which is different from Example 1 only in that the Fe content in the aluminum alloy raw material is 0.8wt%, and the rest is the same as Example 1.

[0077] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 7.5%, a fine grain structure with a proportion of 47.6%, a coarse grain structure with a proportion of 44.7%, and a phase size of the AlFe phase with a phase size of 7.9 micrometers.

[0078] Comparative Example 4

[0079] This comparative example provides a method for preparing an aluminum alloy foil with a heterogeneous structure, which is different from Example 1 only in that the hot rolling temperature in step (2) is 450° C., and the rest is the same as Example 1.

[0080] The aluminum alloy foil has an ultra-coarse grain structure with a proportion of 4.3%, a fine grain structure with a proportion of 58.6%, a coarse grain structure with a proportion of 36.6%, and a phase size of the AlFe phase with a phase size of 13.2 micrometers.

[0081] Test method:

[0082] 1. Grain size test: The samples were tested using an Oxford electron backscattering instrument equipped with a scanning electron microscope (Zeiss, model Sigma 300), and the results were analyzed using post-processing software Aztec Crystal to obtain the equivalent circle diameter of the sample, which was used as the grain size of the sample.

[0083] 2. AlFe phase size test: The sample was tested using a scanning electron microscope (Zeiss, model sigma300), 10 areas were randomly selected, and the phase size of these 10 areas was analyzed using Image-Pro Plus 6.0 software to obtain Diameter (max) data, which was used as the AlFe phase size.

[0084] 3. Method for determining the proportion of fine grains, coarse grains and ultra-coarse grains: 10 areas are randomly selected from the sample, and the size of each grain in each area is counted. The grains with a grain size of less than or equal to 5 microns are considered fine grains, the grains with a grain size between 8 microns and 20 microns are considered coarse grains, and the grains with a grain size of more than 20 microns and less than 60 microns are considered ultra-coarse grains. The number of fine grains, coarse grains, ultra-coarse grains and overall grains in each area is counted. The ratio of the number of fine grains in each area to the number of overall grains is taken as the fine grain ratio of this area, and the average of the fine grain ratios of the 10 areas is taken as the fine grain ratio of the entire sample. The ratio of the number of coarse grains in each area to the number of overall grains is taken as the coarse grain ratio of this area, and the average of the coarse grain ratios of the 10 areas is taken as the fine grain ratio of the entire sample. The ratio of the number of ultra-coarse grains in each area to the number of overall grains is taken as the ultra-coarse grain ratio of this area, and the average of the ultra-coarse grain ratios of the 10 areas is taken as the ultra-coarse grain ratio of the entire sample.

[0085] 4. Y content: Aglient5800 inductively coupled plasma spectrometer was used to test the Y content.

[0086] 5.Fe content: tested in accordance with GB / T7999-2015 standard, using Thermo Fisher Scientific direct reading spectrometer.

[0087] 6. Tensile strength R m , the elongation after fracture A50 is tested according to GB / T228.1-2010 standard, and the testing instrument is ZWICK universal material testing machine.

[0088] The test results of the above embodiments and comparative examples are shown in Table 1.

[0089] Table 1

[0090]

[0091]

[0092] From Table 1, we can see the following points:

[0093] (1) It can be seen from Examples 1 to 3 that the aluminum alloy foil with a heterogeneous structure provided by the present invention can have both high strength and high elongation by forming a heterogeneous structure and controlling the ratio of fine-grained structure to coarse-grained structure in the heterogeneous structure within a reasonable range.

[0094] (2) Effect of AlFe phase size

[0095] By comparing Example 1, Example 2 and Example 4, it can be seen that in Example 2, the Fe element with a content higher than 1.65wt% is introduced, and the size of the final AlFe phase is too large. The hot rolling temperature in Example 4 is low, which makes it difficult to effectively refine the aluminum-iron phase, and there is also a large-sized AlFe phase. Finally, both Example 2 and Example 4 cause the strength and elongation of the material to be seriously reduced. This shows that the present invention can significantly improve the strength and elongation of the aluminum alloy foil by controlling the hot rolling temperature and the content of the Fe element to control the size of the AlFe phase within the range of ≤10 microns.

[0096] (3) Influence of the proportion of ultra-coarse grains

[0097] By comparing Example 1 and Comparative Examples 3-4, it can be seen that when the Fe content in Comparative Example 3 is too low, the proportion of ultra-coarse crystals is too large; and the hot rolling temperature in Comparative Example 4 is low, which also leads to an excessively large proportion of ultra-coarse crystals. Finally, the strength and elongation of the materials in Comparative Examples 3-4 are lower than those in Example 1. It can be seen that the Fe content and the unreasonable control of the hot rolling process jointly affect the number density of the AlFe phase, thereby reducing its number density, and further causing the coarse crystals to grow more easily into ultra-coarse crystals. This shows that the present invention can significantly improve the strength and elongation of the aluminum alloy foil by controlling the hot rolling temperature and the Fe element content to control the proportion of ultra-coarse crystal structure within a range of no more than 5%.

[0098] (4) Influence of the ratio of fine-grained structure to coarse-grained structure

[0099] By comparing Example 1, Examples 5 to 6, and Comparative Example 1, it can be seen that when the Y element with a content of less than 0.01% is introduced in Example 5, the proportion of fine crystals formed is insufficient; in Example 6, the annealing temperature is too low, and although the system is completely recrystallized, the proportion of fine crystals is small; Comparative Example 1 does not contain Y, and the final heterogeneous structure contains about 0.3% of the grain size less than 8 microns. The proportion of such grain structure is small and can be basically ignored; from the comparison of the grain morphology of Comparative Example 1 and Example 1, it is found that the formation of fine grains depends on the heterogeneous nucleation promoted by the precipitation phase containing Y. The decrease in the proportion of fine grains in Examples 5 to 6 and Comparative Example 1 leads to a decrease in the tensile strength and elongation after fracture of the aluminum alloy, which shows that the present invention controls the formation of fine grains by controlling the Y element content and the annealing process, so that the obtained material has better tensile strength and elongation after fracture.

[0100] By comparing Example 1 and Example 4, it can be seen that when the content of the Y element introduced in Example 4 is higher than 0.03%, the proportion of fine crystals formed is relatively too large, and compared with Example 1, the elongation after fracture in Example 4 is significantly reduced.

[0101] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An aluminum alloy foil with a heterogeneous structure, characterized in that: The material of the aluminum alloy foil is an aluminum-iron alloy, and the aluminum-iron alloy contains the Y element; The aluminum alloy foil has a heterogeneous structure, which is mainly composed of fine-grained structure and coarse-grained structure, and the proportion of the ultra-coarse-grained structure does not exceed 5%; wherein the grain size of the fine-grained structure is less than or equal to 5 microns, the grain size of the coarse-grained structure is between 8 and 20 microns, and the grain size of the ultra-coarse-grained structure is greater than 20 microns and less than 60 microns.

2. The aluminum alloy foil with a heterogeneous structure according to claim 1, characterized in that: The proportion of fine-grained structures in the heterogeneous structure is 42% to 56%; and / or the proportion of coarse-grained structures in the heterogeneous structure is 40% to 53%.

3. The aluminum alloy foil with a heterogeneous structure according to claim 1, characterized in that: In terms of mass percentage, the content of the Y element is 0.01-0.03wt%; the content of the Fe element is 0.95-1.65wt%.

4. The aluminum alloy foil with a heterogeneous structure according to claim 3, characterized in that: The maximum size of the AlFe phase is ≤10 microns.

5. A method for preparing an aluminum alloy foil having a heterogeneous structure according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) subjecting an aluminum alloy ingot to homogenization treatment to obtain a homogenized sample; (2) After the homogenization treatment in step (1), the sample is sequentially hot-rolled and cold-rolled to obtain a rolled alloy; (3) The rolled alloy in step (2) is annealed to obtain a finished aluminum alloy foil.

6. The preparation method according to claim 5, characterized in that: The hot rolling temperature is 460-500° C., and / or the total reduction of the hot rolling is 80%-93%.

7. The preparation method according to claim 5 or 6, characterized in that: The annealing temperature is 280-300° C., and / or the annealing time is 1-6 hours.

8. Use of the aluminum alloy foil with a heterogeneous structure as claimed in any one of claims 1 to 4, and / or the aluminum alloy foil made from the aluminum alloy foil with a heterogeneous structure as claimed in any one of claims 5 to 7 in battery soft packaging.

Citation Information

Patent Citations

  • High-performance aluminum foil for lithium ion battery flexible package flexible package film and preparation method thereof

    CN111118351A